Sustainability and innovation : the next global industrial revolution - Haggar, Salah M. El- (Cairo ; New York : The American University In Cairo Press, 2015)
Sustainable development; environmental policy; economic aspects.
Keywords: Sustainable development; Environmental policy -- Economic aspects